Leveraging Virtualization Technology in Teaching Cyber Security Courses in Sub-Saharan Africa - Keyamo, Clement Amone; Ejeh, Patrick Ogholuwarami; Iyoha, Daniel Osamwonyi (Universitas Sebelas Maret, 2023)
Teaching and learning can be effective and enjoyable if the course is well-packaged and presented. This was the experience of students and teachers participating in our hands-on Cyber Security course. Effective teaching of Cyber Security requires practical demonstration of attack patterns and their related countermeasures. This implies that outstanding and modern laboratories must be in place to teach and learn the necessary principles and practices effectively. Unfortunately, newly established universities in Sub-Saharan Africa need more funds for establishing and maintaining such laboratories. However, several researchers have shown that virtualization technology (VT) can enhance available but limited physical computing laboratories as an alternative to complex physical laboratories with huge procurement costs. This paper proposes an ad hoc and mobile laboratory for teaching practical principles in Cyber Security. The report aims to demonstrate the effectiveness of virtualization technology in teaching Cyber Security in newly established universities in Sub-Saharan Africa with zero to minimal computer laboratory infrastructure.